Centralizing an ecological sport psychology through science-practice dialectics - Schinke, R. J.; Li, Y.; Ge, Y.; Zhang, L.; Gao, Q.; Steadman, E. A.; Wang, Y.-B.; Zou, L. (Asian Journal of Sport and Exercise Psychology, 2024)
There has been considerable discussion for more than 50 years of how scientists and practitioners in elite level sport can work collaboratively to ensure that evidence-based practice augments the sport performance and human development of elite amateur and professional athletes. The bridging of these two, often disparate competencies, science and practice, though considered at the conceptual level, continues to be scarcely evidenced within the international sport science community. Much of the research that frames the experiences of elite athletes and their consequent needs, is heavily influenced by scientists, often without direct reciprocity to bridge science, theory, and applied context. The knowledge influencing these interventions has derived from qualitative methods, such as semi-structured interviews, surveys, and focus groups, as well as a breadth of psychometric assessments. Though these approaches to gathering robust data are a necessary part of inquiry, they often produce decontextualized data collection strategies and results, which can lead to generalized, ineffective practices in sport performance environments. Within this submission, the first author cooperated with an international team of scientist-practitioners who are well versed in elite sport to delineate ecologically sound science-practice reciprocity. The authors consider the strengths and weaknesses of conventional qualitative research strategies in terms of their utility and the parlance of evidence into intervention and world-class performance. Two emerging, context driven approaches to inquiry are proposed; arts-based methods and an idiosyncratic approach to ethnography to encourage the reader toward an expanded selection of inquiry approaches from which better understanding and intervention can be generated. This contribution conclude with summary points to open further possibilities for innovative science to practice approaches.